The Meaning of Money as a Determinant of Voting Behavior in Jember: A Phenomenology Study - Haressa Lintang Rizkika; Iffan Gallant EL Muhammady (Empat Sembilan Publisher, 2024)
In today's Indonesia, organizing a democratic party's general election (election) is commonly referred to as